Oral Delivery of mRNA Vaccine by Plant-Derived Extracellular Vesicle Carriers - Margherita A. C. Pomatto; Chiara Gai; Federica Negro; Lucia Massari; Maria Chiara Deregibus; Francesco Giuseppe De Rosa; Giovanni Camussi (Cells, 2023)
mRNA-based vaccines were effective in contrasting SARS-CoV-2 infection. However, they presented several limitations of storage and supply chain, and their parenteral administration elicited a limited mucosal IgA immune response. Extracellular vesicles (EVs) have been recognized as a mechanism of cell-to-cell communication well-preserved in all life kingdoms, including plants. Their membrane confers protection from enzyme degradation to encapsulated nucleic acids favoring their transfer between cells. In the present study, EVs derived from the juice of an edible plant (Citrus sinensis) (oEVs) were investigated as carriers of an orally administered mRNA vaccine coding for the S1 protein subunit of SARS-CoV-2 with gastro-resistant oral capsule formulation. The mRNA loaded into oEVs was protected and was stable at room temperature for one year after lyophilization and encapsulation. Rats immunized via gavage administration developed a humoral immune response with the production of specific IgM, IgG, and IgA, which represent the first mucosal barrier in the adaptive immune response. The vaccination also triggered the generation of blocking antibodies and specific lymphocyte activation. In conclusion, the formulation of lyophilized mRNA-containing oEVs represents an efficient delivery strategy for oral vaccines due to their stability at room temperature, optimal mucosal absorption, and the ability to trigger an immune response.